Pengaruh Biological Asset Intensity, Cash Holding, Dan Leverage Terhadap Biological Asset Disclosure: Studi pada Perusahaan Agrikultur yang Terdaftar Di Indeks Saham Syariah Indonesia (ISSI) Periode 2017-2023 - Andriansyah, Rizki; Nurlaili; Ermawati, Liya (Indonesian Journal of Islamic Economics and Business, 2025)
The Central Bureau of Statistics (BPS) notes that the agricultural sector has consistently contributed more than 10% to Indonesia's Gross Domestic Product (GDP) in the past decade, with the figure reaching around 12.53% in 2023. Biological assets are plants and animals owned by companies as a result of past activities and have the potential to provide economic benefits in the future. This study aims to analyse the effect of Biological Asset Intensity, Cash Holding, and Leverage on Biological Asset Disclosure. The population of this study are agricultural companies listed on ISSI in the 2017-2023 period. The sample in this study used purposive sampling, so that a total sample of 8 companies from 10 observation data was obtained. This study uses the classical assumption test and multiple linear regression analysis (MRL). The results in this study indicate that Biological Asset Intensity with a significant value of 0.047 and Leverage with a significant value of 0.004 has a positive and significant effect on Biological Asset Disclosure. While Cash Holding has a negative and insignificant effect on Biological Asset Disclosure with a significant value of 0.294. Simultaneously Biological Asset Intensity, Cash Holding, and Leverage have a positive and significant effect on Biological Asset Disclosure with a significance value of 0.000.